Measurement of Heavy Metal Mercury (Hg) Content in The Swamp Eel (Monopterusalbus) as a Bioindicator from Lake Rawa Taliwang - Dinda Noviantika; Khairuddin Khairuddin; M. Yamin (Jurnal Penelitian Pendidikan IPA, 2024)
The presence of heavy metals in Lake Rawa Taliwang can originate from various activities in the upstream river, around settlements, and within the lake itself. Mercury (Hg) is a highly toxic heavy metal due to its neurotoxic nature, affecting both organisms and humans. One of the fish found in Lake Rawa Taliwang is the swamp eel. Swamp eels are often caught for consumption and cultured by the local community. This study aims to determine the mercury (Hg) concentration in swamp eels (Monopterus albus) and assess their suitability for consumption. Sampling was conducted using purposive sampling technique at two stations with two replications at each station. Data analysis involved determining mercury concentration in the swamp eel samples using Atomic Absorption Spectroscopy (AAS). The results showed that the mercury concentration in swamp eels from Lake Rawa Taliwang was 0.13 mg/kg. According to the BPOM regulation no. 9 of 2022, the mercury concentration in these swamp eels is still below the permissible limit for metal contamination in food. This indicates that swamp eels were taken from Lake Rawa Taliwang is safe for consumption.